A dyadic study of adult romantic attachment and relationship quality - Tadinac, Meri (Array, 2008)
A close relationship between two persons is characterised by their interaction and the effect they have on each other. Although it is obvious that characteristics and behaviour of one partner influence the change in the other partner, most researchers disregard this interaction and base their conclusions about the relationship on the data from only one of the partners. Dyadic research takes into account characteristics of both partners and their interaction, therefore offering more meaningful insight in interpersonal relationships. The aim of this study was to determine the role of the attachment dimensions of both partners in their positive interactions, as well as the impact of these variables on the perceived relationship quality. Since the data from our previous research suggest that the effect of attachment style on relationship quality decreases with the duration of relationship, it was necessary to take the relationship duration into account. The sample consisted of 418 adult couples from three major cities in Croatia. Relationship duration varied from 1 to 54 years. Dyadic analyses were conducted to determine the impact of each individual’ s and partner’ s variables, as well as their interaction, on the perceived relationship quality. Results are discussed with respect to the prototypic and revisionist perspective on the attachment theory.